Protein and Digestible Threonine Levels in Pre Starter Diets for Broiler Chicks - Brito , Alexandre Barbosa de; Stringhini, Jose Henrique; Filho, Roberto de Moraes Jardim; Xavier, Suzany Aparecida Gomes; Cafe, Marcos Barcellos; Leandro, Nadja Susana Mogyca (International Journal of Poultry Science, 2013)
This experiment was carried out in experimental poultry facilities of University of Goias to estimate digestible threonine (Thr) requirement for broiler from 1 to 21 days of age. 384 AgRoss-508 broiler chicks were allotted in a completely randomized design in a 4 x 2 factorial arrangement, with two protein levels (205 and 221 g/kg) and four digestible threonine levels (6.1, 7.1, 8.1 and 9.1 g/kg) with four replications of 12 birds each. The performance, nutrient digestibility and morfometrical index were evaluated. The polynomial regression and linear response plateau (LRP) model was used to estimate digestible, had been the Minimum Square of Deviations (MSD) utilized for choice criterion. Used polynomial regression, the results showed that a quadratic effect (p<0.05) for mean body weight at seven and 21 days of age (seven days - Y = -31.41 + 455.28x - 285.62x2/21 days - Y = 510.08 + 508.91x - 324.61x2) which estimates a 7.9 and 7.1 g/kg of digestible Thr, but LRP model showed low MSD and smaller estimates for digestible Thr levels (7.7 and 6.7 g/kg in seven and 21 days, respectively). The results showed a tendency if lower levels of digestible Thr (below to 7.1 g/kg) reduced intestinal length. The digestible Thr levels recommended for pre-starter phase vary from 7.7 at 6.7 g/kg, estimated by LRP model and 7.9 at 7.1 g/kg estimated by polynomial regression for mean body weight at seven and 21 days of age, respectively, but the LRP values presented smaller minimum square of deviations.